Crowdfunding: A Spimatic application of digital fandom. (February 2015) - Booth, Paul
The digital environment has opened up new spaces for fans to engage with the production process of their favoured texts. However, fan studies have largely neglected the larger temporal structures undergirding this engagement. In this article, I augment studies of digital fandom by utilizing Bruce Sterling's technosocial concept of the Spime as a means of investigating the relationship forged between the technology of crowdfunding and the affect of particular audiences. The successful Kickstarter campaigns for Rob Thomas and Kristen Bell's Veronica Mars film and Zach Braff's film Wish I Was Here, and the failed Kickstarter campaign for Melissa Joan Hart's film Darci ' s Walk of Shame, each illustrate how the entertainers drew (or did not draw) on specific support from the lineage of his or her own fan communities to generate funds and word-of-mouth publicity. These campaigns ultimately illustrate the consequential powers of the fan at multiple nodes within the production process.